2013
DOI: 10.1261/rna.038893.113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EJC-enhanced and EJC-independent NMD in human cells reveals two partially redundant degradation pathways

Abstract: Nonsense-mediated mRNA decay (NMD) is a eukaryotic post-transcriptional gene regulation mechanism that eliminates mRNAs with the termination codon (TC) located in an unfavorable environment for efficient translation termination. The best-studied NMD-targeted mRNAs contain premature termination codons (PTCs); however, NMD regulates even many physiological mRNAs. An exon-junction complex (EJC) located downstream from a TC acts as an NMD-enhancing signal, but is not generally required for NMD. Here, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 107 publications
7
127
0
1
Order By: Relevance
“…We therefore conclude that SMG6-and SMG7-mediated degradation routes appear to be two highly redundant branches of the mammalian NMD pathway. This is consistent with previous observations made with reporter genes (Luke et al 2007;Jonas et al 2013;Metze et al 2013) and in line with what was observed in a study focusing on SMG6 endonucleolytic activity (Schmidt et al 2015). In ′ UTR features between NMD targets and a matched control group.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore conclude that SMG6-and SMG7-mediated degradation routes appear to be two highly redundant branches of the mammalian NMD pathway. This is consistent with previous observations made with reporter genes (Luke et al 2007;Jonas et al 2013;Metze et al 2013) and in line with what was observed in a study focusing on SMG6 endonucleolytic activity (Schmidt et al 2015). In ′ UTR features between NMD targets and a matched control group.…”
Section: Discussionsupporting
confidence: 93%
“…7G). We observed that the codepletion of both proteins resulted SMG7 recruits the CCR4-NOT complex to NMD targets in a synergistic inhibition of NMD, leading to a 30-fold increase in the b-globin PTC reporter levels, as previously reported (Luke et al 2007;Jonas et al 2013;Metze et al 2013). This effect was prevented by the expression of a shRNA-resistant version of SMG7, which partially restored NMD (Fig.…”
Section: The Smg7 Pc Region Functions Redundantly With Smg6supporting
confidence: 83%
“…Briefly, an shRNA targeting the ORF of the smg5 mRNA was used to deplete endogenous SMG5 in cell lines constitutively expressing a well-characterized NMD reporter based on the b-globin gene (Thermann et al 1998). Because SMG6 can partially compensate for the absence of SMG5 (Jonas et al 2013;Metze et al 2013), we depleted SMG6 in combination with SMG5. SMG5 and SMG6 codepletion resulted in a 12-fold increase in the level of b-globin PTC mRNA (Fig.…”
Section: Smg5 Requires Interaction With Smg7 To Function In Nmdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the exon-junction complex (EJC) components that provide the recognition platform for NMD, the CB accumulated UPF1/RENT, which is a key mediator of NMD, SMG1 kinase, which activates UPF1 through phosphorylation, and SMG6, which is an endonuclease involved in the NDM pathway (Huntzinger et al 2008;Eberle et al 2009;Kervestin and Jacobson 2012). SMG1-mediated UPF1 phosphorylation (and the subsequent dephosphorylation) was recently shown to be the only critical requirement for both, EJC-enhanced and the alternative, EJC-independent NMDs (Metze et al 2013). It is important to note that according to our immunofluorescence results, the CB-localized UPF1 is at least partially phosphorylated.…”
Section: Discussionmentioning
confidence: 99%